Cold Creek Manor [videorecording (DVD)] - Quaid, Dennis; Stone, Sharon, 1958-; Dorff, Stephen, 1973-; Lewis, Juliette; Stewart, Kristen, 1990-; Plummer, Christopher; Quinn, Declan, 1957- (Touchstone Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2004)
The Tilsons are a wealthy couple who have grown tired of the high stress of life in New York City and are looking to move. Upstate, they find a mansion in the village of Cold Creek which has fallen into disrepair after it was repossessed. Convinced the house has great possibilities, the Tilsons buy it, and with a little hard work they are soon living in their dream home. Before long the family begins to learn the disturbing truth about the history of the mansion.